RELATIONSHIP BETWEEN KNOWLEDGE OF QUADRATIC FUNCTIONS AND PERFORMANCE IN MATHEMATICS OF FRESHMAN COMPUTER TECHNOLOGY STUDENTS: PROPOSED MEASURES FOR IMPROVEMENT - Garciano, Homer P; Delos Santos, Ma. Salud M (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 11 No. 1-2, 2008, 2008)
The main purpose of this study was to find out whether there was a relationship between the knowledge of quadratic functions and the performance in mathematics of the freshman Bachelor of Science in Industrial Technology – Computer Technology (BSIT – CT) Students of the Cebu State College of Science and Technology – Fishery and Industrial College (CSCST – FIC), San Francisco, Cebu. The study used the descriptive method using correlational research with follow – up interview after a 20- item teacher- made test was administered to the respondents. There were 61 respondents that were given the test about their knowledge of quadratic functions. The results of this test were treated and analyzed. Then it was paired with the respondent’s performance in mathematics in order to determine the degree of relationship between them. The findings revealed that there was a low positive correlation between the respondents’ knowledge of quadratic functions and the performance in mathematics. Then this relationship was found out to be significant after it was statistically tested for its significance. The findings also revealed that the respondents’ performance in mathematics was found out to be on the above average category, while their knowledge of quadratic function was in the poor category. Proposed measures for the improvement in the performance in mathematics of the freshman Computer Technology Students will be highly recommended so that maximum learning of the students in mathematics specifically quadratic functions would be achieved.